1998
DOI: 10.1002/(sici)1097-0231(19980630)12:12<773::aid-rcm231>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-programmed desorption for membrane inlet mass spectrometry

Abstract: We present a novel technique for analyzing volatile organic compounds in air samples using a solid adsorbent together with temperature-programmed desorption and subsequent detection by membrane inlet mass spectrometry (TPD-MIMS). The new system has the advantage of a fast separation of compounds prior to the detection by MIMS. The gaseous sample is simply adsorbed on the adsorbent, which is then rapidly heated from 30°C to 250°C at a rate of 50°C/min. Trapped organic compounds are released from the adsorbent i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…We explore this concept in this paper and term it single-sided membrane introduction mass spectrometry (SS-MIMS). The single-sided membrane inlet combines the features of trap and release MIMS [14][15][16][17] with surface partitioning. Note that the single-sided membrane introduction technique is based on similar physical principles to solid phase extraction (SPE) and solid phase microextraction (SPME), a commonly utilized offline adsorption/desorption technique for extraction, preconcentration, and introduction of samples into gas chromatographs.…”
Section: Introductionmentioning
confidence: 99%
“…We explore this concept in this paper and term it single-sided membrane introduction mass spectrometry (SS-MIMS). The single-sided membrane inlet combines the features of trap and release MIMS [14][15][16][17] with surface partitioning. Note that the single-sided membrane introduction technique is based on similar physical principles to solid phase extraction (SPE) and solid phase microextraction (SPME), a commonly utilized offline adsorption/desorption technique for extraction, preconcentration, and introduction of samples into gas chromatographs.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work36 on the analysis of complex mixtures of VOCs, we demonstrated that temperature programming of a sorbent trap in front of the membrane could be used to create a fast chromatographic separation of the compounds prior to MIMS analysis. It is likely that something similar can be done with the analysis of solid materials in a hot cell whose temperature is ramped relatively quickly.…”
Section: Resultsmentioning
confidence: 99%
“…For better identication of mixed substances in water, a temperature-programmed desorption (TPD) unit may be used. It has been reported that TPD-MIMS can completely separate a number of similar VOCs in air, 14 however there are currently no published results available for TPD-MIMS in water. Table 1 presents a summary of all the organic species from the NIST library that were tested in water with our mobile mass spectrometer.…”
Section: View Article Onlinementioning
confidence: 99%